Back to Megalith Era as a Concept of Eco-Friendly Megalith Edutourism Design in Bondowoso - Wahyuni, Sri; Maslucha, Luluk; Subaqin, Agus (Proceedings of the International Conference on Green Technology; Vol 9 No 1 (2018): Proceeding of the 9th International Conference on Green Technology 2018, 2019)
Bondowoso is a regions in Indonesia which has the most megalithic sites. Based on the data of the megalithic sites in 2017 had been found around 1123 sites, however about 40% of these site are poorly preserved and some were missing. Therefore, an interesting edutourism design as the megalith information center, protection, research, educational places and tour are needed. The concept back to megaliths era of Megalithic edutourism presents the atmosphere of travel in the megalith era for visitors so that visitors feel a different atmosphere in every of its spatial. The concept back to megaliths era still produces the draft of friendly environment approached by applying the traditional strategy transformation in the design process. Evolutionary traditional transformation of the Meander’s river and megalithic site with external , internal and artistic boundaries as well as applying the transformation principles in order the resulting design of megalith edutourism is friendly environment, despite presenting a megalithic atmosphere.